2003
DOI: 10.2460/ajvr.2003.64.506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humeral osteotomy on joint surface contact in canine elbow joints

Abstract: Humeral osteotomies alter joint surface contact areas of the canine elbow joint in vitro. Humeral osteotomies may decrease contact areas on the diseased region of the joint in dogs with elbow dysplasia; however, the overall decrease in joint surface contact area suggests that these procedures may induce focal increases in pressure that may cause iatrogenic cartilage damage when applied in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 24 publications
3
78
0
2
Order By: Relevance
“…Associations between degree of cartilage generation and clinical outcome associated with high tibial osteotomy in humans have not been reliably documented. 31,34 The secondary changes recognized in medial gonioarthrosis of the human knee joint resemble in nature and extent the cartilage changes seen in MCD of the canine elbow and have been demonstrated to occur because of chronic overloading of the medial compartment [23][24][25] . Radioulnar step defects, humeroulnar incongruence, mechanical radioulnar-humeral varus deformity, or imbalances between skeletal and muscular mechanics may all contribute to medial compartment overload of the canine elbow.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Associations between degree of cartilage generation and clinical outcome associated with high tibial osteotomy in humans have not been reliably documented. 31,34 The secondary changes recognized in medial gonioarthrosis of the human knee joint resemble in nature and extent the cartilage changes seen in MCD of the canine elbow and have been demonstrated to occur because of chronic overloading of the medial compartment [23][24][25] . Radioulnar step defects, humeroulnar incongruence, mechanical radioulnar-humeral varus deformity, or imbalances between skeletal and muscular mechanics may all contribute to medial compartment overload of the canine elbow.…”
Section: Discussionmentioning
confidence: 98%
“…Fujita et al 25 noted that individual variation between limbs was substantial, so biomechanical predictors may be difficult to fully elucidate. Mason et al 24 suggested that abduction or adduction of the limb during weight bearing could also be associated with significant variations in biomechanical load distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have demonstrated the efficacy of humeral osteotomies in transferring load bearing forces toward the relatively healthy lateral joint compartment, 63,64 with force at the proximal articular surface of the ulna being decreased after SHO of 4 and 8 mm by 25% and 28% respectively. 64 Outcomes of clinical application in 59 elbows have been positive, and arthroscopic (Fig 11) and histologic documentation of novel fibrocartilaginous cover of previously eburnated regions has been achieved.…”
Section: And Extensive Medial Humeral Condylar Kissing Lesionmentioning
confidence: 99%